Combining transcriptomics-based and proteomics-based approaches for functional characterization of terpene synthases of “Arnica da Serra” (Asteraceae) - Pavarini, DP; Oliveira, LP; Pereira, LM; Natsui, AP; Spring, O; Lopes, NP (Planta medica, 2013)
Lychnophora ericoides (Vernonieae: Asteraceae), known as “Arnica-da-serra”, is restricted to Brazilian “Cerrado” and is used for wound healing. Its leaves produce a range of volatile sesquiterpenes original from the bisabolyl cations, also known as bisabolene-like derivatives. We have recently reported the bioactivity of essential oil fraction against invertebrate Acari (BALDIN et al., 2010) and the in vitro anti-hyper nociceptive ability of a major compound (PAVARINI, 2011). Enzymes behind the biosynthesis of these sesquiterpenes are usually the target of researches that are pushing the boundaries of natural products biosynthesis. This achievement often leans on the results of enzymes functional characterization. Our previous results were achieved through targeted-proteome searches by MALDI imaging highlight the perspective of protein mapping on plant tissues (PAVARINI, et al., 2012). Simultaneously, the biotechnology panorama is tied very tightly to fundamental sciences knowledge. Therefore, we are combining research fields at this present work in order to move towards a comprehensive description of these volatile sesquiterpenes biosynthesis pathway. Our efforts have been concentrated in the main subjects: (1) to achieve plant protein maps by using gel-based separation of protein extracts; (2) to reach protein identity information by spots digestion protocols, mass spectrometry and chemo informatics-based inventories; (3) to access transcripts encoding genes of terpene synthases; (4) to isolate the transcripts and amplify them; (5) to get these genes expressed using transfected microorganisms. We expect a bright outlook for generating combined molecular images of enzymes and metalolites using MALDI imaging to be settled at the end of this work. References: [1] Baldin, E.L.L. et al., Bolet. San. Veg. Plag., 36 , 125, 2010. [2] Pavarini, D.P. 126 p. Master's Dissertation, FCFRP-USP, University Of São Paulo, 2011. [3] Pavarini, D.P. et al., Plant. Med., 78 , 1027, 2012.